Assessing the need for spiritual care and evaluating the usefulness of a spiritual assessment tool in a multicultural population of patients with life threatening illnesses in South Africa - Blanchard, Charmaine Louise (Department of Public Health and Family Medicine, 2015)
Includes bibliographical references (leaves 69-71).